(untitled) - Haley, Alex (New York, N.Y., 1976)
This poignant and powerful narrative tells the dramatic story of Kunta Kinte, snatched from freedom in Africa and brought by ship to America and slavery, and his descendants. Drawing on the oral traditions handed down in his family for generations, the author traces his origins back to the seventeen-year-old Kunta Kinte, who was abducted from his home in Gambia and transported as a slave to colonial America. In this account Haley provides an imaginative rendering of the lives of seven generations of black men and women.
Keywords: African American families,Gia đình người Mỹ gốc Phi